Diversification of Nila Fish Products in the Mina Mandiri Bokesan, Sindumartani, Ngemplak - Ernoiz Antriyandarti; Susi Wuri Ani (Trunojoyo University of Madura, 2022)
Bokesan hamlet, Sindumartani, Ngemplak, Sleman is known as Kampung Nila. There is the Mina Mandiri group, which consists of mothers whose main production is Nila floss. In order to increase income, product diversification is required. Therefore, participatory action research was carried out aimed at creating productive economic activities in the Mina Mandiri group to increase household income, by providing training in processing Nila into crackers, nuggets and meatballs. To support production activities, equipment assistance in the form of a cake pan, food processor, meat grinder, vacuum sealer and pressure cooker was provided to the Mina Mandiri group in Bokesan, Sindumartani, Ngemplak, Sleman. After empowerment activities, the Mina Mandiri group has been able to produce fish crackers, fish nuggets and fish balls, thereby increasing the diversification of processed fish products.